1996
DOI: 10.1063/1.470749
|View full text |Cite
|
Sign up to set email alerts
|

The dynamics of symmetric polystyrene–polybutadiene diblock copolymer melts studied above and below the order–disorder transition using dynamic light scattering

Abstract: This communication describes dynamic light scattering measurements on three low molar mass symmetric polystyrene–polybutadiene diblock copolymer melts. Above but close to the order–disorder transition, four modes contribute to the time-dependent correlation function. In the depolarized geometry there is a very fast, broad relaxation typifying the segmental reorientational dynamics and a slower, single-exponential mode related to chain orientation and stretching. In the polarized experiments two additional proc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
23
0

Year Published

1997
1997
2003
2003

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(25 citation statements)
references
References 39 publications
2
23
0
Order By: Relevance
“…The details of the motional dynamics above and/or close to T ODT were deduced from DLS experiments by Papadikis et al [17] on the same symmetric diblock copolymer of low molecular mass. Above the T ODT the copolymers melts exhibit more than one relaxation mode which reflect the inhomogeneity of the copolymer.…”
Section: Esr Spectra Of Bzono Probe In Block Copolymersmentioning
confidence: 99%
See 1 more Smart Citation
“…The details of the motional dynamics above and/or close to T ODT were deduced from DLS experiments by Papadikis et al [17] on the same symmetric diblock copolymer of low molecular mass. Above the T ODT the copolymers melts exhibit more than one relaxation mode which reflect the inhomogeneity of the copolymer.…”
Section: Esr Spectra Of Bzono Probe In Block Copolymersmentioning
confidence: 99%
“…The mobility of copolymer chains is commonly assessed by dynamic mechanical measurements [12], nuclear magnetic resonance [13 -16], dynamic light scattering (DLS) [17], dielectric spectroscopy [18] and dynamic infrared linear dichroism spectroscopy [19]. However, one of the method which can also offer an insight into the dynamics properties and microphase separation of block copolymers is electron spin resonance (ESR) using nitroxide spin probes as molecular reporters [20,21].…”
Section: Introductionmentioning
confidence: 99%
“…Measurements were conducted in the polarized geometry. The measured intensity correlation functions G 2 (t) were analyzed by inverse Laplace transformation using the routine REPES [28] together with a subtraction routine described in references [15,29]. From the distribution functions of relaxation times, τ A(τ ) vs. log(τ ), the mean relaxation times of each mode were extracted as the centers of mass of each peak.…”
Section: Dynamic Light Scatteringmentioning
confidence: 99%
“…As the amplitude of the internal mode is proportional to N 2 (for Gaussian chains), it is usually not observed for block copolymers having low molar masses. Two additional dynamic processes have been observed experimentally in symmetric diblock copolymers: a second diffusive mode, termed X-mode, tentatively attributed to undulations of the lamellar interfaces or to the diffusion of small amounts of homopolymer [11,12], and a q-independent mode giving rise to depolarized scattering as well, attributed to the rotation of stretched chains [13][14][15] or to the reorientational dynamics associated with the largeamplitude composition fluctuations near the ODT [12]. Also, the segmental reorientational dynamics and largescale heterogeneities ("clusters") have been observed (e.g., [15]).…”
Section: Introductionmentioning
confidence: 99%
“…[38 -44] The temperature dependence of diffusion coefficients for HASE can be described by the Arrhenius relationship. [40,41] The slope in the plot of ln (D) versus 1/(RT) yields the activation energies, which provides a measure of the energy needed to overcome the energy barrier for the diffusion of particles. It is found that E a for unimers and aggregates in the HASE-EO35C1 system are 8.3 kJ/ mol and 5.2 kJ/mol respectively.…”
Section: Effect Of Salt Concentrationmentioning
confidence: 99%